Fiber-reinforced polymer composites in strengthening reinforced concrete structures: A critical review. (1st November 2019) - Naser, M.Z.; Hawileh, R.A.; Abdalla, J.A.
Highlights: Review of Fiber-reinforced polymer (FRP) composites in infrastructure is presented. Performance of FRP strengthening systems in extreme conditions is reviewed. Limitations, challenges, and research needs associated with FRPs are discussed. Abstract: Fiber-reinforced polymer (FRP) composites continue to provide designers with the ability to deliver innovative and intelligent solutions to overcome the ever-growing aging issues in infrastructure. Since it has been more than 50 years to the introduction of FRP materials to the construction industry, this paper presents a state-of-the-art review on historic and recent developments of FRP in strengthening and rehabilitation of civil engineering applications. This review highlights some of the classic and modern experimental, numerical, and analytical studies associated with the integration of FRPs into buildings, among other structures. The discussion presented herein aims at covering application of FRP systems in reinforced concrete structural members and also highlights the performance of FRPs (including bonding agents) under extreme conditions such as elevated temperature, saline environment, and cycles of freezing and thawing. This paper also presents a collective perspective on number of limitations, challenges and research needs associated with successful, sustainable, and durable implementation of FRPs in civil infrastructure.